Optimalisasi Penetrasi Internet bagi Intensitas Pelaksanaan Rapat Anggota Tahunan (RAT) dan Peningkatan Volume Usaha Koperasi (Studi Koperasi di Provinsi Jawa Timur, Provinsi Jawa Tengah, dan Provinsi Jawa Barat) - Sonoto, John Fery (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2021)
This study aims to simulate the contribution of internet penetration to the intensity of the implementation of the Annual Membership Meeting (RAT) and the achievement of business volume by cooperatives. The research methodology is literature study and field study. Researchers conducted a study of the contribution of internet penetration, the implementation of RAT and the achievement of business volume, especially in the regions of East Java Province, Central Java Province and West Java Province from 2017 to 2019. West Java Province has not optimally utilized the contribution of internet penetration to carry out RAT and has not optimally used the internet as a business process strategy to generate business volume in the receipt of cooperative goods and services compared to the Provinces of East Java and Central Java. This research is limited to the areas of West Java, Central Java and East Java Provinces. The contribution of this research to the implementation of the adoption of information and communication technology for the board and management team of cooperatives in Indonesia in preparing to welcome the digitization of cooperatives in Indonesia so as to strengthen internal cooperatives in making business decisions for sustainable cooperative development.